A Roadmap to Developing a Population-Based Colorectal Cancer Screening Program in Oman - Rashid AlKalbani, Salma; Smith, Alan (Journal of Public Health International, 2024)
Colorectal cancer (CRC) is a major public health problem worldwide, as it is the third most common disease and the second leading cause of cancer-related fatalities. In recent years, Oman, like many other countries, has seen an epidemiological shift from communicable diseases to noncommunicable diseases, including colorectal cancer, necessitating comprehensive planning to address the root cause of the problem as well as a comprehensive screening program to detect diseases at an early stage and thus improve health outcomes. Colorectal cancer is the second most frequent cancer in Oman, with the highest mortality rate, inflicting considerable public health and economic consequences; nevertheless, there is no population-based CRC screening programme in place to minimise the disease's incidence, mortality, and severe health outcomes. This review highlights the epidemiology of colorectal cancer in Oman, the Wilson and Junger criteria, operational readiness, and recommendations for implementing a population-based colorectal cancer screening program.
Keywords: colorectal cancer; population-based screening program; Oman